2009
DOI: 10.1007/s00264-009-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

Early migration characteristics of a hydroxyapatite-coated femoral stem: an RSA study

Abstract: Measurement of early stem subsidence can be used to predict the likelihood of long-term femoral component loosening and clinical failure. Data that examines the early migration pattern of clinically proven stems will provide clinicians with useful baseline data with which to compare new stem designs. This study was performed to evaluate the early migration pattern of a hydroxyapatitecoated press-fit femoral component that has been in use for over ten years. We enrolled 30 patients who underwent THA for osteoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 23 publications
13
72
2
1
Order By: Relevance
“…5 Their results showed subsidence of 0.23-3.71 mm at a mean of 2 years follow up. Majority of the subsidence was reported to occur within the first 6 months after surgery (mean 0.5 mm) and less than 0.3 mm further subsistence was seen between 6 and 24 months.…”
Section: 58-10mentioning
confidence: 96%
See 1 more Smart Citation
“…5 Their results showed subsidence of 0.23-3.71 mm at a mean of 2 years follow up. Majority of the subsidence was reported to occur within the first 6 months after surgery (mean 0.5 mm) and less than 0.3 mm further subsistence was seen between 6 and 24 months.…”
Section: 58-10mentioning
confidence: 96%
“…One potential limitation of any uncemented femoral stem is the risk of early subsidence or migration leading to loosening and implant failure. [4][5][6][7] Berend reported that the early subsidence of femoral stem was associated with higher revision rate. 4 However, Krismer et al reported an increased incidence of early subsidence but better subsequent stability and good long-term results.…”
Section: Introductionmentioning
confidence: 99%
“…There is no study that has investigated the cut-off of 60 points for surgery, but a preoperative HHS below 60 points has been found in several studies evaluating patients with hip OA for THR. 11,24 Power calculations were based on knee extension muscle strength only, possibly resulting in a lack of statistical power for some of the other variables measured in this study. patients with hip OA who participated in these earlier studies had severe hip OA and might have had larger muscle strength deficits.…”
Section: Key Pointsmentioning
confidence: 99%
“…An initial subsidence and migration into retroversion, which stabilized later, has been described using RSA for a clinically well-proven cementless stem (Hallan et al 2007, Campbell et al 2011). Continuous migration has been associated with inferior results for cemented stems (Kärrholm et al 1994).…”
Section: Discussionmentioning
confidence: 99%